Challenges Affecting Human Resource Development In The Civil Service Organizations In Sudan - Salih, Atif Mohamed Ahmed (2011)
There are many dimensions that can influence the nature of human resource development (HRD). Despite the differences in the definitions of HRD, the common themes are focusing on the development of knowledge and skills of people as the central factor. Many of the studies focused on a complex range of activities aiming at achieving different organizational objectives. In this study, working environment is considered to be the most essential factor for HRD, employees’ satisfaction and organizational productivity. In Sudan, employees’ need important major issues represent their expectations from their organizations, which in turn lead to an environment of cooperation, motivation to work, enhancement of performance and increase in productivity. Majority of the employees of the civil service in Sudan are dissatisfied with their jobs and the civil service is unable to play its entire role in the economic development. Training and organizational environment are having effects on employees’ productivity and organizations’ performance. The purpose of this study is aimed at shedding some light on the challenges that affect HRD in civil service organizations in Sudan especially with regard to training and working situations. The study targeted the middle and senior professionals and non-professionals employees.